Un amigo en la ciudad - Aparicio-Belmonte, Juan, 1971- (Madrid : Siruela, 2013)
Andrés is in love with Gretchen, the same fair-skinned girl with whom he used to get in trouble when they both belonged to that Gothic urban tribe, and with whom he now cohabitates and has a daughter. One day he notices that everything around him has changed and the past and the future aren't where he thought they were.
Online resource; title from ePub title page (Digitalia, viewed April 1, 2016)
Keywords: Mind and reality -- Fiction; Psychological fiction; Electronic books